Pengaruh Konten Media Instagram @tempodotco terhadap Partisipasi Politik Digital Gen Z di Indonesia - Rini Rahyuni; Indra Lestari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This study aims to analyze the influence of @tempodotco's Instagram media content on Generation Z's digital political participation in Indonesia. This study uses a quantitative approach with an explanatory design. Data were collected through a survey using a structured questionnaire distributed online to 100 Generation Z respondents selected using a purposive sampling technique. Data were analyzed using inferential statistics with Pearson correlation tests and simple linear regression to determine the direction and magnitude of the influence between variables. The results show that @tempodotco's Instagram media content has a significant and positive influence on Generation Z's digital political participation in Indonesia. The coefficient of determination indicates that media content is able to explain some of the variation in digital political participation, while the rest is influenced by other factors outside the research model. These findings suggest that exposure to credible and critical independent media content can encourage young people's political engagement in the digital space. This study concludes that social media not only functions as an information channel but also as an important space for political participation for Generation Z. The results of this study are expected to contribute to the study of digital political communication and become a consideration for online media in developing strategies for presenting effective and relevant political content for the younger generation.